Lead Induced Oxidative Stress and Affected the Expression of Steroidogenesis -related Genes in Testis of Male Mice - Nahla Abdalla Hassan Elsheikh; Nagmeldin Abd elwahid. Omer; Li-lian; Gen-Lin Wang (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Lead (Pb) is classified as a major risk factor affecting the male reproductive system; however, itsprecise mechanisms of action are poorly understood and inconsistent. This work aimed to investigate the effect ofPb toxicity on male reproductive function.Methods: Accordingly, in this study, adult male mice treated with Lead acetate (PbAc) by gavage (200 mg/kg/day) for 28 days. We analyzed sperm count and morphology, oxidative stress, and the expression of antioxidantand steroidogenesis -related genes in the testes of male mice.Results: Pb significantly (P<0.05) showed decreased body weight and sperm count, as well as significantly(P<0.05) increased the number of abnormal sperms and plasma testosterone level. The activities of superoxidedismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (Cat) were significantly decreased, whereasthe level of malondialdehyde (MDA) was significantly increased in the testis of mice treated by Pb. The mRNAlevels of antioxidant-related genes (SOD1, GPX1, and CAT) were significantly decreased following Pb treatment.Furthermore, the expression of genes involved in the steroidogenic pathway, including steroidogenic acuteregulatory protein (Star), cytochromeP-450scc (Cyp11a1), 17β-Hydroxysteroid dehydrogenase (17β-HSD),3β-Hydroxysteroid dehydrogenase (3β-HSD) and cytochrome P450, family 17 (Cyp17), were significantly (P<0.05)decreased after exposure to Pb.Conclusion: In conclusion, Pb disrupts male reproductive function by inducing oxidative stress, negativelyregulating the mRNA expressions of steroidogenesis and antioxidant -related genes, and ultimately reducingsperm quality and quantity.